DFT-guided synthesis of N, B dual-doped porous carbon from saccharina japonica for enhanced oxygen reduction catalysis - Zhang, Junjie; Wu, Chao; Wang, Jilong; Xia, Maosong; Li, Shixin; Liu, Long; Wei, Wuguo; Peng, Xing (Frontiers in Chemistry, 2024)
Oxygen reduction reaction (ORR) is a crucial determinant of the energy transformation capacity of fuel cells. Six models using density functional theory demonstrate that N, B dual-doping carbon exhibits superior ORR performance compared to either N or B doping carbon. A highly efficient dual-doped carbon ORR catalyst (S-850-1) is synthesized, derived from saccharina japonica and containing N (4.54 at%) and B (1.05 at%). Electrochemical analysis reveals that S-850-1 significantly outperforms N mono-doping carbon S-850 (0.838 V and -5.24 mA cm⁻²), exhibiting a higher half-wave potential (0.861 V) and greater limited current density (-5.60 mA cm⁻²). S-850-1 surpasses the 20% Pt/C in performance, exhibiting enhanced durability and exceptional resistance to CO and methanol. An LED light may be powered by the 1.40 V open circuit voltage that S-850-1 produces when integrated into a Zn-air battery. Both theoretical and practical evaluations validate the excellent ORR performance of N, B dual-doping carbon, as evidenced by the agreement between the electrochemical results and DFT calculations. In addition to extending the range of ORR catalysts made from biomass, this work offers guidance on how to create and produce affordable, effective catalysts that make use of natural resources.